Antibiotic susceptibility of common bacterial pathogens in urinary tract infections in a teaching hospital in Southwestern Nigeria (2011)
"Urinary tract infection (UTI) is one of the most common bacterial infections in humans and a major cause of morbidity. However, the aetiology of UTI and their antibiotic sensitivity patterns vary from time to time and across different areas. This study determines the frequently isolated UTI bacteria from inpatients and out-patients of a Teaching hospital in Southwestern Nigeria and their antibiotic susceptibility patterns. Sixty (60) bacterial isolates from urine of patients with significant bacteriuria in UTI were collected and evaluated for their antibiotic sensitivity using modified Kirby-Bauer method. UTI was frequently encountered in females (61.7%) and older patients (50%). 55% of the isolates were from in-patients. The most common etiological organisms of UTI were Esherichia coli (46.7%), Pseudomonas aeruginosa (18.3%), Klebsiella spp (13.3%), Staphylococcus aureus (13.3%) and Proteus spp (6.7%). Pseudomonas aeruginosa was found only among hospital isolates while Staphylococcus aureus was isolated from females only. Antibiotic susceptibility pattern revealed that the Enterobacteriaceae were highly susceptible to Ciprofloxacin (71.4 to 75%) while Nitrofurantoin demonstrated the best activity against S. aureus isolates (100%) in both community and hospital acquired UTI. All the isolates exhibited high degree of resistance to Augmentin and amoxicillin. High rate of multi-drug resistance was recorded among all isolates. In view of the increasing rate of resistance of UTI pathogens to commonly used antibiotics, rational prescription and use of antibiotics is advocated."